2007
DOI: 10.1177/230949900701500319
|View full text |Cite
|
Sign up to set email alerts
|

Management Outcome and the Role of Manipulation in Slipped Capital Femoral Epiphysis

Abstract: Patients with acute or acute-on-chronic SCFE can be safely managed with straight-leg traction for up to 6 days, followed by in situ screw fixation without manipulation. Manipulation is not recommended in such slips, due to a higher avascular necrosis risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 23 publications
0
15
0
4
Order By: Relevance
“…Overall, 23.9% of patients developed osteonecrosis but the reported ranges varied from 0% to 58% (Table 2). Only two articles established diagnostic radiographic criteria for osteonecrosis [18,22], and only three studies documented the timeframe for establishing the diagnosis of osteonecrosis [13,16,18]. For 13 studies, the minimum length of followup was 12 months (average, 36 months; range, 12-72 months).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, 23.9% of patients developed osteonecrosis but the reported ranges varied from 0% to 58% (Table 2). Only two articles established diagnostic radiographic criteria for osteonecrosis [18,22], and only three studies documented the timeframe for establishing the diagnosis of osteonecrosis [13,16,18]. For 13 studies, the minimum length of followup was 12 months (average, 36 months; range, 12-72 months).…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies did not report complications. Two studies reported clinical outcomes data using unvalidated measures [8,13] and one study reported radiographic outcomes for patients who developed osteonecrosis using Stulberg's classification for healed Legg-Calve-Perthes [18].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…32e34 In-situ fixation is considered as the most safe surgical technique regarding vascularization 30,32 but its functional result could be worse because of partial reduction of upper femoral deformity. Preoperative traction is not risky 8,35,36 or has no real benefit. 5 Numerous pins or screws and upper extern quadrant localization of pins or screws are also considered as risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…A number of treatments options were reported for the study population including epiphysiodesis [10,11], pinning in situ (PIS) [1,7,[12][13][14][15][16][17][18][19], closed reduction and pinning (CRIF) [4,5,11,15,16,18,[20][21][22][23][24][25], open reduction and physeal osteotomy (PO) [1,7,15,26] open reduction and internal fixation (ORIF) [23][24][25]27] and surgical dislocation (SD) [13,15,[28][29][30].…”
Section: Description Of Studiesmentioning
confidence: 99%